The long term results of modified Gittes operation in patients with stress incontinence - Ozsan, Ozcan; Sariyuce, Oguzhan; Ozbek, Emin; Balbay, Derya; Gunes, Ali (Annals of Medical Research, 2021)
None
Keywords: s : Incontinence, female, surgery, Gittes